Data hiding technique in steganography for information security using number theory. (December 2019) - Rehman, Amjad; Saba, Tanzila; Mahmood, Toqeer; Mehmood, Zahid; Shah, Mohsin; Anjum, Adeel
In the current era, due to the widespread availability of the Internet, it is extremely easy for people to communicate and share multimedia contents with each other. However, at the same time, secure transfer of personal and copyrighted material has become a critical issue. Consequently, secure means of data transfer are the most urgent need of the time. Steganography is the science and art of protecting the secret data from an unauthorised access. The steganographic approaches conceal secret data into a cover file of type audio, video, text and/or image. The actual challenge in steganography is to achieve high robustness and capacity without bargaining on the imperceptibility of the cover file. In this article, an efficient steganography method is proposed for the transfer of secret data in digital images using number theory. For this purpose, the proposed method represents the cover image using the Fibonacci sequence. The representation of an image in the Fibonacci sequence allows increasing the bit planes from 8-bit to 12-bit planes. The experimental results of the proposed method in comparison with other existing steganographic methods exhibit that our method not only achieves high embedding of secret data but also gives high quality of stego images in terms of peak signal-to-noise ratio (PSNR). Furthermore, the robustness of the technique is also evaluated in the presence of salt and pepper noise attack on the cover images.